Hubungan Penggunaan Media Sosial dengan Perilaku Sedentari pada Dewasa Awal (20-24 Tahun) di Kota Medan - Silalahi, Novitasari Wijayanti; Rochadi, R. Kintoko; Andayani, Lita Sri (UI Scholars Hub, 2025)
Background. Non-Communicable Diseases (NCDs) are caused by four risky lifestyle behaviors, one of which is sedentary behavior. Sedentary behavior involves activities that expend minimal energy. Several factors are associated with sedentary behavior, including technological advancements. One of the most time-consuming technological advancements is excessive use of social media, leading to addiction. Aim. This study aims to determine the relationship between social media addiction with sedentary behavior among young adults (aged 20-24 years) in Medan City. Method. The research design was cross-sectional study. A total of 271 respondents were selected using accidental sampling. The data were analyzed using simple linear regression tests.. Result. The average score of social media usage is 18 (on a scale of 30). There is a significant positive relationship between social media usage and sedentary behavior in early adults. The p-value is 0.001, the correlation coefficient is 0.43, and the regression coefficient is 190.67. It can be concluded that the higher the level of social media addiction, the higher the sedentary behavior in early adults.